Field-scale depositional evolution of the Upper Jurassic Arab Formation (onshore Abu Dhabi, UAE). (January 2018) - Marchionda, Elisabetta; Deschamps, Rémy; Cobianchi, Miriam; Nader, Fadi H.; Di Giulio, Andrea; Morad, Daniel J.; Al Darmaki, Fatima; Ceriani, Andrea
Abstract: The paper aims to provide a new field-scale depositional model for the Upper Jurassic Arab Formation, in order to enlarge the stratigraphic and facies architecture knowledge in the onshore Abu Dhabi (UAE). The goal is reached following a threefold workflow structured by: (i) subsurface high-resolution facies analysis; (ii) well correlations; and (iii) paleofacies maps. The facies analysis was based on 540 m of cores and 277 thin sections. Eighteen facies were defined, and were grouped into five facies associations, representative of a shallow marine carbonate ramp succession. The ramp ranges from outer ramp to supratidal and intertidal environments, with a shoal complex protecting a lagoon. A micropaleontological approach helped at defining the field-scale evolution of the different sedimentary environments through time and space. The results were integrated with well log data (Gamma Ray and Density-Neutron Log), and were used to establish the stacking pattern of the Arab Formation. The vertical and lateral distribution of the facies associations in the area of study were highlighted by the well correlations. These latter were useful to generate several new paleofacies maps corresponding to key stratigraphic surfaces identified within the succession. The model reveals different directions of progradation, suggesting a local topographic control on the deposition of the Arab Formation. The cyclical arrangement of the facies associations and the peculiarities of this new model have been discussed at regional scale, suggesting a new paleogeographic scenario. Highlights: A new field-scale depositional model of the Arab Formation is proposed. Different directions of progradation are detected at the local scale. Local controls on accommodation/relative sea level are discussed. A new paleogeographic picture is suggested at the regional scale for the Arab Formation.